Tracción vertebral en el tratamiento fisioterapéutico de hernia discal y dolor lumbar - Jocelyne Dayanara, Piedra Arévalo (2021)
ABSTRACT This research was a bibliographic review, the same one that aimed to investigate up-to-date information on vertebral traction in patients with herniated disc and lumbar pain to promote immediate recovery, alleviate the symptomatology provided by said pathology, and in this way improve the quality of life of patients. This study found 75 scientific articles under the criteria of assessment and exclusion according to the SCALE of PEDro. They were discarded or accepted, and through the flowchart, 35 items that had greater validity and scientific rigor were taken into account. These meet an assessment greater than or equal to 7 points according to the scale of PEDro. The original articles were in languages such as English and Spanish. Using the information of these studies allows this research to help corroborate the effectiveness of vertebral traction in patients with herniated disc and lower back pain. The databases used to obtain this studies' information were PubMed, Scielo, MedLine, Travell and Simons publications, Google Scholar, and virtual libraries of university repositories. Concluding this research project, after the authors' discussion, it was possible to verify the effectiveness of the application of vertebral traction in the physiotherapeutic treatment of herniated discs and lumbar pain. It reduces pain caused by bad postures or excessive weight loads, thus improving patients' quality of life. Keywords: Vertebral traction, herniated disc, lower back pain, quality of life. Reviewed by: Ms.C. Ana Maldonado León ENGLISH PROFESSOR C.I.0601975980